Guidelines on assigning the subjects of theses and dissertations in repositories - Fujita, Mariângela Spotti Lopes [UNESP]; Panuto, Jessica Cristina [UNESP] (SAGE Publications, 2024)
This study aims to investigate how Brazilian institutional repositories guide subject representation in the self-archiving of their information resources. As a method, an exploratory and qualitative study was carried out with the application of an electronic exploratory analysis of repositories and an analysis of transcripts of thesis and dissertation authors’ Individual Verbal Protocols during self-archiving. The analysis of the results in the Brazilian university repository sample shows that 10 have a self-archiving policy and five include guidance to the author on subject representation and metadata quality. The transcription analysis of the authors’ Individual Verbal Protocols reveals that all authors consider keywords important for content representation. The investigation concludes that the self-archiving process is fundamental for the dissemination of scientific information and wide access to the community.
Keywords: institutional repositories; Self-archiving; subject representation